Modeling and analysis of millimeter-wave propagation in dusty environments - Farhad E. Mahmood; Fawaz Y. Abdullah (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2022)
In the fifth generation of wireless communication systems (5G), the millimeter wave (mmWave) signal can be affected by many challenges in irregular environments such as dust and sand storms. In this paper, we investigate the attenuation that faces a mmWave link signal in a dusty environment for different sizes of dust particles. Further, we derive a model to calculate the total attenuation in mobile communication systems and/or internet of things (IoT) in different base stations highnesses. The obtained results show that in a dusty environment it is better to have high base station transmitters as the signal may escape the dense dust area. The paper also studies the case of the city of Mosul to find that not only the dry weather is increasing the attenuation, but wet weather also may impact more on the attenuation in the mmWave systems.